A numerical FEM solution of gear root stress in offset axial mesh misalignment - Lias, M.R. (2013)
Gear offsets mesh in axial misalignment always leads to unevenness of load transferred contributing the impact of stress value and distribution along important critical path of the tooth root. Its happening due to overpress fitting when the gear is mounted onto the shaft as an interference hub fit. Current design methodology based on empirical model provide solution by approximation load factor fail to attributes in detailed regarding this phenomenon This paper determined to focus on this phenomenon in term of methodology to the stress distribution at the critical contact region of the tooth root of the gears. Pair of spur gear with real geometrical construction and condition was constructed with offset parameter. A moving load quasi-static model with a numerical FEM solution using ANSYS is presented with modification in loading variation. For verification, the stress value at the critical path of the tooth root is compared between standard high point single tooth contacts (HPSTC) loading to moving load model. As the result, a numerical FEM methodology to calculate the stress distribution of the gear tooth root in offset axial misalignment with moving load model approach is determined. The proposed method is also found reliable as an alternative solution to define an accurate load factor calculation compared to the approximation provided by the standard empirical procedure. Â© (2013) Trans Tech Publications, Switzerland.